Charming or alarming?: a study into the relationship between propensity for stalking, abusiveness and theory of mind - Perkins, Martha Kate (2017)
Stalking is a form of harassment characterised by repeated and unwanted intrusive behaviours, resulting in victims becoming fearful and significantly emotionally and psychologically distressed. Factors noted to have been implicated in stalking behaviour are prior relationships - intimate or otherwise - with the victim, and violence and abusiveness. Research suggests that in some cases, stalkers are not aware of how their victims are feeling. Theory of mind (ToM) is the ability to infer the mental states of others, and research into this area with offenders shows that offenders possess some ToM deficits, but not in all cases. The present study aims to identify the presence of a relationship between ToM, propensity for stalking and propensity for abuse. 121 participants completed scales pertaining to propensity for stalking and abusiveness, and completed a ToM task. Data were analysed using descriptive statistics, Pearson’s correlation and linear multiple regression. It was found there was no significant effect of ToM ability on stalking propensity, but there was a significant relationship found between propensity for stalking and propensity for abuse. Further avenues for research include conducting the test on a forensic population, or comparing different stalking contexts such as cyberstalking.